Characteristics of Legal Reasoning in Cases Regarding Liability of Internet Intermediaries - Baltrimas, Johanas (Teisė, 2022)
The paper is focused on identifying criteria for legal reasoning used by courts in disputes regarding internet intermediary‘s liability for offences committed by someone else. There are cases with this atypical phenomenon when a person, who did not infringe someone else‘s individual rights, is held liable, e. g. liability of an internet platform‘s operator for unlawful comments posted by the visitors. The paper presents an analysis of criteria for legal reasoning which carry potential to be used in the future when new disputes related to technological innovation reach courts.